Effect of In-Plane Biaxial Compression Force on Penetration Resistance for Steel Plate - Mahmood, Najdat Asker; Salem, Mohammed Zakaria Salah (Nahrain University College of Engineering Journal, 2008)
The importance of penetration and perforation in to targets in both military and civilian applications has made it the subject of many investigations. But the bulk of these investigations was experimental rather than analytical or numerical because of complexity of the governing equations. Hence most of the existing models are either mathematically rigorous or so simplified that they neglect many important parameters. Moreover, weight and cost are among the most important consideration in the design of perforation resistant systems (containment shields). Therefore, the present investigation has focused on the perforation and penetration of relatively thick metallic targets by rigid cylindro-ogival projectiles. To achieve the experimental part of this work a locally manufactured compression device was built for this purpose where the target plate was subjected to biaxial compression load of about 0.6 of its buckling load. A life 7.62 mm ammunition with steal projectiles have been used to impact the targets at 400 and 600 m/s thus the exit velocity in terms of the impact velocity and the total work done at the target was derived for the case of biaxial compression. Comparison of the experimental and the analytical results showed a good agreement while targets in the state of compression showed about 80% improvement in penetration resistance